2004
DOI: 10.1111/j.1600-0501.2004.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Study on the necessity for cross‐section imaging of the posterior mandible for treatment planning of standard cases in implant dentistry

Abstract: The information from preoperative cross-sectional spiral tomography has minor impact on treatment planning in standard implant cases in mandibular premolar and molar regions. The clinical examination provides sufficient information for selecting implant diameter and the panoramic radiograph provides sufficient information for implant length selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 26 publications
3
81
1
5
Order By: Relevance
“…[12][13][14][15][16] In our study, we found changes in length in about 60% of cases not using CBCT (40% remained unchanged), similar to the results by Schropp et al 13 who found changes in 70% of cases. Ekestubbe and Grondahl 12 detected a 70% agreement in the dimensions of the selected implants, between the planning stages, using conventional tomography and the dimensions at surgery, similar to our results (69.5% agreement for length and 73.7%, for width).…”
Section: Discussionsupporting
confidence: 91%
“…[12][13][14][15][16] In our study, we found changes in length in about 60% of cases not using CBCT (40% remained unchanged), similar to the results by Schropp et al 13 who found changes in 70% of cases. Ekestubbe and Grondahl 12 detected a 70% agreement in the dimensions of the selected implants, between the planning stages, using conventional tomography and the dimensions at surgery, similar to our results (69.5% agreement for length and 73.7%, for width).…”
Section: Discussionsupporting
confidence: 91%
“…4 It is widely used as a standard radiographic examination tool in implant treatment, [1][2][3][4] and allows evaluation of the available bone height before inserting posterior mandibular implants. [4][5][6] Taking into account the panoramic unit's magnification factor, 5 and in accordance with the recommendations for implants placed above the inferior alveolar nerve, a safety margin of at least 2 mm between the implant's tip and the mandibular canal is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Furthermore, panoramic radiographs have been reported to be sufficiently reliable to evaluate the available bone height before inserting posterior mandibular implants. [4][5][6] Image distortion, due to variations in the degree of magnification in the horizontal and vertical planes, is well described for conventional film-based panoramic radiography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is then worrying that there is such a frequent use of CT (53% of the respondents prescribing cross-sectional imaging) among the respondents. It has been widely recorded by many researchers [21][22][23] that if bone width and lingual undercut can be estimated suffi ciently well during clinical examination then a panoramic fi lm is accurate enough to obtain the information regarding implant length. Therefore, this CT frequency could be attributed to the availability of the device in regional hospitals or even over-zealousness, or worse still manufacturer-generated implant drillguidance software.…”
Section: -S E C T I O N S I N T H E M a X I L L A ( M U L T I P L Ementioning
confidence: 99%